(untitled) (Revista Española de Derecho Internacional, 2006)
The article takes care of some aspects of the legal regulation of the recognition of intercountry adoptions in Spain. It analyzes the DGRN Resolution of 15th july 2006 on the recognition and registration of international adoptions in the Spanish Civil Registry in the following subjects: control of the jurisdiction of the foreign authority, control of the law applied by the foreign authority, treatment of the recognition of “simple” adoptions, mandatory character of the Convention of 29 May 1993 on Protection of Children and Co-operation in respect of Intercountry Adoption, or the law applicable to the condition to adopt. Also, the author requests for a regulation adapted to the acces of intercountry adoptions to the Civil Registry.